An Accessible Interface Layer for Self-Sovereign Identity - Lockwood, Mick (Frontiers in Blockchain, 2021)
The mechanisms and evolving standards collectively known as Self-Sovereign Identity (SSI) offer the prospect of a decentralised Internet by providing a central pillar for a Human-Centred Data Ecosystem (HCDE). Once established this technology promises to afford participants the same agency in the digital realm as individuals experience in the real world. Investigation suggests that the domain is now sufficiently mature to realise practically the principles of SSI, but in order to achieve sustainable adoption significant design focused work needs to be undertaken at the interface layer. This paper presents recent practice led research designed to project current SSI prototypes to scale through conceptual modelling, preliminary user interface, and critical analysis. This research introduces the term Sovereign Boundary Mechanism (SBM), a standardised collection of SSI interactions, which can be described as a metaphorical ring of sovereignty between the participant and the wider network. Within this model, participants control identity, relationships, data streams, and access control. This research identifies the domains of interaction and the minimum required objects for a full-scale SSI engagement through an SBM. It defines the component parts and functionality of a wider HCDE which require further consideration, and it identifies emergent concepts for which a participant may lack mental model and understanding. The research considers Human Computer Interaction (HCI) theory across internalised, external and distributed cognition, arguing that the current trajectory of SSI requires significant internalised representations, prior knowledge and participant responsibility. This research argues that these elements are problematic and pose a significant barrier to sustainable adoption. In conclusion this research suggests that the decentralised community need to recognise the obstacle potentially posed at the interface layer, and engage in collective standardisation, strategy and design thinking to increase the probability of sustainable adoption.